THE 'REBORN' PHENOMENON OF A FORMER PRESIDENT: NAVIGATING LEADERSHIP LEGACY AND POLITICAL SHADOWS IN A NEW ERA - Leonanda, Benny Dwika (Politik Indonesia: Indonesian Political Science Review, 2024)
The "reborn" phenomenon of former President Joko Widodo (Jokowi) following the conclusion of his term has introduced a new dynamic into Indonesian politics. Unlike most former leaders who opt to retreat from the public eye to focus on personal or spiritual pursuits, Jokowi remains actively engaged in various public activities. His consistent presence, warmly received by the public, has sparked speculation about the motivations behind his involvement and its implications for the new administration under President Prabowo Subianto. Jokowi’s continued visibility in the public sphere raises concerns about the potential blurring of authority between the new leadership and the perception that his political influence remains significant even after stepping down. This article seeks to analyse the motivations and impacts of Jokowi’s post-presidency engagement from social, political, and psychological perspectives. Additionally, it explores Javanese cultural traditions, such as the concept of “lengser keprabon madeg pandito ratu,” which underscores the importance of spiritual reflection for former leaders. By understanding this historical and cultural context, this study aims to provide insights into how a former leader can maintain relevance in modern Indonesian politics and the implications for political stability and power consolidation during the transition to a new administration.